Pengaruh Trust Dan E-Service Terhadap Repurchase Intention Bagi Pengguna Aplikasi Shopee - Nilasari, Reni (E-Jurnal Akuntansi; Vol 29 No 2 (2019)DO - 10.24843/EJA.2019.v29.i02.p20, 2019)
Modern applications certainly require a neatly arranged system, making it easier for consumers to use it. Trust is an important thing that online sites need because logically consumers have a higher level of risk in online transactions compared to offline transactions in terms of shipping, payment, and personal information. The purpose of this study is to find out how trust and e-service can affect Repurchase intention in shopee application users. Analysis using multiple regression with data from this study 128 respondents shopee application users. The result is trust and e-service have a positive effect on repurchase intention. Keywords : Trust, E-service; Repurchase Intention; Shopee.